KEANEKARAGAMAN JENIS KUPU-KUPU (Subordo Rhopalocera) DI KAWASAN WISATA HAPANASAN ROKAN HULU SEBAGAI SUMBER BELAJAR PADA KONSEP KEANEKARAGAMAN HAYATI - Elya Febrita; Yustina '; Dahmania ' (Biogenesis, 2014)
This study aims to determine species diversity of butterfly (Subordo Rhopalocera) in the tourisms area Hapanasan and designing learning sources are the relevant to biodiversity concept based on these results. Observation were conducted from April to June 2013. Determination of the research station by purposive random sampling, that determined based on differences characteristics of habitat. Station I is a secondary forest area, station II is a tourisms park area, station III is a rubber plantations area and station IV is an oil palm plantations. Biological parameters measured are species composition of butterfly (Subordo Rhopalocera) and species diversity index of butterfly (Subordo Rhopalocera). The measured physical parameters include are temperature, humidity and wind speed. Based on the results of the study, founded 194 individual of butterflies. They are consist of 60 species belong to 5 families include Hesperiidae (2 species), Papilionidae (10 species), Pieridae (9 species), Nymphalidae (36 species) and Lycaenidae (3 species). The highest number of species were founded at station II, station IV, station III and the lowest founded at station I. The highest species diversity index were founded at station II (H '=3.23), and the lowest at station I (H '=2.10). The collection and photo of speciments can be used as a source of biology learning in senior high school class X on the biodiversity concept. Learning sources that made media insectarium, syllabus, lesson plans and worksheets.Keyword: Butterfly, Diversity, Hapanasan, Learning sources